Gastrointestinal Stromal Tumors: Molecular Mechanisms and Targeted Therapies. (21st February 2011) - Downs-Kelly, Erinn; Rubin, Brian P.
Abstract : Gastrointestinal stromal tumors (GISTs) are the most common mesenchymal neoplasms of the gastrointestinal tract and are diverse not only in their clinical behavior but also in their histologic appearance. GISTs are insensitive to conventional sarcoma chemotherapy and radiation. However GISTs are sensitive to small-molecule tyrosine kinase inhibitors as 85–90% of GISTs have KIT or platelet-derived growth factor receptor alpha (PDGFRA) mutations, which drive tumorigenesis. This review will briefly touch on the clinicopathological features of GIST, while the majority of the review will focus on the clinical and treatment ramifications of KIT and PDGFRA mutations found in GIST.